Acute Mastoiditis in Children with Cochlear Implants: Is Explantation Required?. (4th June 2014) - Zawawi, Faisal; Cardona, Isabel; Akinpelu, Olubunmi V.; Daniel, Sam J.
Abstract : Objective: Acute mastoiditis is an uncommon but challenging condition when it occurs in children with cochlear implant. The literature is scarce as to the management of this condition with regards to explantation. The objective of the study is to determine the need for explantation in patients with cochlear implants who suffer from acute mastoiditis. Data Sources: Online medical databases—PubMed, Ovid Medline, Ovid Medline in process, Embase, Cochrane Library, CINAHL, Biosis, Google Scholar, and Scopus. Review Methods: A systematic review of all publications addressing the treatment of mastoiditis in cochlear implant children prior to November 2013 was conducted. Data were collected from online medical databases—PubMed, Ovid Medline, Ovid Medline in process, Embase, Cochrane Library, CINAHL, Biosis, Google Scholar, and Scopus. The review was performed in 3 phases; an initial screening review of abstracts was performed, followed by a detailed review of full articles based on inclusion and exclusion criteria, and lastly a final review to extract data from selected articles. Results: Twelve articles were found eligible for this systematic review including a total of 43 patients. Subperiosteal abscess was present in 14.3%. All patients received intravenous antibiotics as an initial treatment, and if needed, surgical intervention was performed. Only 1 patient required explantation (2.3%). Conclusion: Prompt, aggressive medical and if needed surgical therapy can help in saving the implant and result in a favorable outcome.